Desenvolvimento de queijo cottage simbiótico - Paródia, Carline Gass (2010)
The growing popularity of functional foods, has promoted advances in the research of new products, specially in the dairy industry. The objective of this study was to evaluate the influence of different levels of fat and inulin on the physicochemical and sensorial characteristics, instrumental color and texture, and viability of probiotic cultures of cottage cheese with the addition of Streptococcus termophilus, Lactobacillus acidophilus La - 5 and Bifidobacterium Bb 12, during storage for 21 days at 4 ± 1 °C. Twelve treatments of cottage cheese were elaborated with different fat and inulin concentrations according to a central composite design with 4 repetitions on the central point. Significant changes were observed on the physicochemical characteristics (tritable acidity, protein, fat, salt, moisture and ash) due to the different levels of fat and inulin in the cheeses. The assessment of the sensory attributes (global appearance, aroma, texture, acidity and taste) was carried out using a test with hedonic scale of 7 levels and an ordering test. The surface response showed different areas with tendency to better acceptance, varying according to the sensory attribute, in spite of no significant difference having been found by Tukey s test (p> 0.05). Only the linear and interaction of multiple linear regression terms were significant (p< 0.05) for the aroma sensory attribute; only the intercept of the equation of each attribute was significant (p< 0.05). The differences in the lipid profile were related to different fat levels in each formulation. The surface response was done to verify the influence of different levels of fat and inulin on pH and tritable acidity during storage; only linear terms of fat and inulin levels were significant (p< 0.05). The pH and tritable acidity affect the viability of the cultures during all the storage period. Streptococcus termophilus, Lactobacillus acidophilus e Bifidobacterium animalis had counts above 7 UFC g-1 during all the period, assuring the probiotic potential in all the cottage cheese formulations. The extent proteolysis increased significantly during storage, but this change has no reduce the firmness of the cheeses. The parameters of instrumental color and texture vary significantly (p< 0.05) between 1 and 21 days of storage for most formulations, but these results did not affect the acceptability of the tasters.